An Adjacency matrix-based Multiple Fuzzy Frequent Itemsets mining (AMFFI) technique - Patel, Mahendra Narottamdas; Shah, Dr. Sanjay M.; Patel, Suresh B (International Journal of Intelligent Systems and Applications in Engineering, 2022)
Recently, discovering helpful information from a database consisting of transactions has been a critical research topic. Several frequent itemsets mining for association rule mining, algorithms that can only handle binary databases have been proposed. Transactions using numerical values, on the other hand, are ubiquitous in real-world applications. Thus, with reference to the quantitative transactional database, several algorithms were developed and “fuzzy frequent itemsets” (FFI) were discovered. Most of them just consider the term having maximum cardinality. As a result, the number of fuzzy regions processed is equal to the number of original elements. Multiple fuzzy zones of an item, on the other hand, give a better result for making a correct decision. This study presents an AMFFI-miner (Adjacency matrix-based multiple fuzzy frequent itemsets) for discovering multiple FFIs out of a quantitative transactional database. Adjacency matrix and fuzzy-list structures were designed to find multiple FFIs by scanning database only ones and lesser candidate itemsets generation. Join two nodes if its co-occurrence between two fuzzy linguistics terms satisfies minsupport threshold by finding the co-occurrence between two fuzzy linguistics terms directly from the adjacency matrix, thus reducing the number of node joining and speeding up discovering multiple FFI. Experiments were carried out to compare the suggested method’s performance to that of existing methodologies on the basis of running time, memory utilization, and the number of nodes joining.